Risk of Developing Compassion Fatigue, Quality of Life, and Satisfaction of Social-Related Professionals (American Journal of Human Psychology, 2025)
The study titled “Risk of Developing Compassion Fatigue, Quality of Life, and Satisfaction of Social-Related Professionals” aims to explore the prevalence and impact of compassion, fatigue, alongside assessing the quality of life and job satisfaction among social-related professionals in the City of Ilagan. The research focused on a diverse group of professionals, including nurses, teachers, police officers, guidance counselors, and lawyers, highlighting the emotional and psychological challenges inherent in these roles. Using a combination of the Compassion Fatigue/Satisfaction Self-Test (CFS) and WHOO\QOL-BREF, data were collected from 381 respondents through structured questionnaires. The results reveal weak correlations but no significance between compassion fatigue and both the quality of life and job satisfaction when suing a 01% significance level. Notably, the findings indicate that high levels of compassion fatigue have a negative impact on the perceived quality of life and job satisfaction among these professionals.